PUNISHMENT EFFICIENCY: RESULTS OF INTERNATIONAL RESEARCH - H. Kury; O. Y. Il’Chenko (Russian Journal of Economics and Law)
Objective: Basing on the analysis of international research data, to show that the atrocity of punishment has an insignificant restrictive and preventive effect on the criminality level. Methods: The dialectic method was used as the general scientific method of cognition, allowing to study the phenomena and processes of ambient reality in their historical development, as well as specific scientific methods, including the historical-juridical, systemic-legal, social-psychological in various combinations. Results: Basing on the carried out analysis of a significant volume of works in the sphere of criminal-procedural, criminal, international law, criminalistics, theory of state and law, as well as results of research carried out in the USA, Finland, Germany, Switzerland, Portugal and Russia, the authors have shown the insignificant influence of punishment on reducing of the criminality level. Scientific novelty: Basing on the analysis of empirical data it is shown that punishment as a means of regulation and prevention of the society member’s undesirable behavior has been used since ancient times. The atrocity sanctions were widely used as early as in the Middle Ages. Nowadays the efficiency of punishment implementation is subject to doubt. Alternative sanctions, as a rule, are as successful, and their implementation is cheaper. Practical value: The theoretical provisions formulated in the research can be used in scientific, law-making and law-enforcement activity, in educational process of higher professional education establishments of juridical sphere, and in up-grading qualification of practical staff and scientific-academic personnel in the sphere of jurisprudence.